Predation and Competition Differentially Affect the Interactions and Trophic Niches of a Neotropical Amphibian Guild - Arribas, Rosa; Touchon, Justin C.; Gomez-Mestre, Ivan (Frontiers in Ecology and Evolution, 2018)
Competition and predation alter individual traits of organisms, and these effects can scale-up to have consequences on community structure and dynamics. The relative importance of competition and predation will depend largely on the local assemblage of species, the type of predators, or the degree of niche segregation. We experimentally investigated the interplay of competition and predation on the structure and trophic level (measured via stable isotope analysis) of a seven-species Neotropical freshwater guild using a mesocosm approach in central Panama. We tested the effect of two types of predators (dragonfly nymphs or adult water bugs) in combination with the presence/absence of a common competitor, the red-eyed treefrog (Agalychnis callidryas), on four core species of tadpoles. We also distinguished between consumptive and non-consumptive effects of each type of predator by presenting them to tadpoles caged or freely roaming. Dragonfly larvae were more efficient predators than water bugs, but these effects were not uniform for all tadpole species. All amphibian species grew bigger when raised in the presence of an uncaged dragonfly nymph, presumably due to reduced competition through thinning, but tadpoles were smaller when exposed to caged dragonfly nymphs indicating the existence of non-consumptive predator effects as well. Predator presence also altered the relative trophic position of the different amphibian species, causing some tadpole species to increase and others to decrease their trophic status. Despite the presumed ecological similarity of tadpole species in the guild, the interplay of competition and predation had varying effects on the trophic status of nearly every species. Our results indicate that community composition can greatly affect the trophic level of larval amphibians, and that predation may have a greater role than competition in structuring Neotropical larval amphibian guilds.